2017
DOI: 10.3892/or.2017.5459
|View full text |Cite|
|
Sign up to set email alerts
|

FoxO3a induces temozolomide resistance in glioblastoma cells via the regulation of β-catenin nuclear accumulation

Abstract: Glioblastoma multiforme (GBM), the most common malignant brain tumor, is currently treated with temozolomide (TMZ), but GBM often exhibits resistance to TMZ. Although several mechanisms underlying GBM resistance to TMZ have been identified, these mechanisms are yet to fully explain how GBM gains resistance to TMZ. Our previous work has shown that FoxO3a, a member of the FoxO subfamily of transcription factors, promotes glioma cell proliferation and invasion. In this study, we sought to determine whether FoxO3a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The oncogenic properties of the transcription factor FOXO3 have been reported in different cancers [2][3][4][5][6][7][8][9][10]. In high-stage NB, FOXO3 promotes tumor angiogenesis in vivo [11] and chemoprotection in vitro [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oncogenic properties of the transcription factor FOXO3 have been reported in different cancers [2][3][4][5][6][7][8][9][10]. In high-stage NB, FOXO3 promotes tumor angiogenesis in vivo [11] and chemoprotection in vitro [12].…”
Section: Discussionmentioning
confidence: 99%
“…In high-stage NB, therapy-failure due to acquired chemoresistance and metastasis formation results in a high relapse rate and a five year survival probability of less than 40% [1]. The transcription factor FOXO3, a member of the forkhead box O (FOXO) superfamily, has been associated with elevated tumorigenicity in different cancers [2][3][4][5][6][7][8][9][10]. In concordance, our own Preparation of protein extracts of SH-EP/FOXO3 cells incubated with 75 nM 4OHT for 8 and 16 h was done as described previously [32].…”
Section: Introductionmentioning
confidence: 99%
“…FOXO-mediated inhibition of cell proliferation has led to the view that these factors have tumor suppressive roles [41], although this view may be too simplistic given what appears to be opposing FOXO function in glioma. A recent study examining FOXO3a expression in patient HGGs suggests a strong association between high expression and poor prognosis [42], while another study using two human GBM cell lines demonstrated that FOXO3a expression induces TMZ resistance [43]. These recent studies in GBM patients and cells, underscore the importance of FOXO in supporting brain cancer cell growth and survival and highlight the potential therapeutic importance of the FOXO transcription factors in HGG.…”
Section: The Pi3k Pathway In Cancermentioning
confidence: 99%
“…FOXO3 has been characterized as tumor suppressor gene based on its anti-proliferative and pro-apoptotic functions [2]. However, an increasing number of studies point out the "dark side" of FOXO3 and describe its potential oncogenic properties in different cancer types, including chronic myeloid leukemia (CML), acute myeloid leukemia (AML), breast cancer, glioblastoma, and pancreatic cancer [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Our own studies demonstrate that nuclear FOXO3 promotes tumor angiogenesis in vivo [18] and chemoresistance in vitro [19] in aggressive NB.…”
Section: Introductionmentioning
confidence: 99%
“…Sykes et al observed active FOXO3 in AML patient samples and demonstrated that conditional deletion of FOXOs in an AML mouse model reduces leukemia-initiating cell function in vivo, improves animal survival, and mediates myeloid maturation and AML cell death [12]. Recent studies indicate that FOXO3 triggers chemoresistance in glioblastoma via the regulation of β-catenin [16] and elevated FOXO3 expression is associated with poor patient prognosis [17]. Yu et al identified FOXO3 as a key regulator in cetuximab resistance in metastatic colorectal cancer [25].…”
Section: Introductionmentioning
confidence: 99%